Prácticas de higiene oral en pacientes con aparatología ortodóntica 2021-I (2021)
To maintain good oral hygiene practices is essential in orthodontic patients. Gaps in oral hygiene practices carries alterations in oral health, among which we have gingivitis, enamel’s decalcification and stains in the vicinity of the therapeutic material in 50-70% of cases.